Thermal and electrical characterization of ZnO based pellets and thin films - Lim, Joon Hoong (School of Materials Engineering, 2016)
The research scope in this thesis may be broadly divided into three parts as: the preparation of the pellets, the fabrication of the thin films and the thermoelectric characterization.